Gender Gaps in Working Conditions. - Antón, José Ignacio; Grande-Martín, Rafael; Muñoz de Bustillo, Rafael; Pinto, Fernando (Springer, 2023)
The evolution of the gender pay gap has received a great deal of attention from academia and public opinion alike, yet our understanding of the differences in non-monetary working conditions is much scarcer. Through the use of the European Working Conditions Survey and six composite indicators of job quality, this research aims to expand our knowledge on the gender gaps in job attributes across the European Union over the period 2005–2015 in three ways: firstly, we explore gender differences in working conditions, revealing the distinct patterns identified by the dimensions of job quality and country; secondly, we find that, on average, women’s relative position deteriorates in terms of the physical environment and working time quality; a result that again reflects considerable heterogeneity across the countries in the sample. Lastly, we find clear evidence of a catch-up process in job quality in all the non-monetary dimensions of working conditions across the European Union.
Keywords: Mujeres - Trabajo; Igualdad de género; Gender gap; Working conditions; Job quality; Europe